2013
DOI: 10.1074/jbc.m112.433185
|View full text |Cite
|
Sign up to set email alerts
|

HECT Domain-containing E3 Ubiquitin Ligase NEDD4L Negatively Regulates Wnt Signaling by Targeting Dishevelled for Proteasomal Degradation

Abstract: Background: Dishevelled is a critical component of Wnt signaling; however, its stability control is not fully understood. Results: NEDD4L regulates Wnt signaling through Dishevelled2 degradation, and Wnt5a-induced NEDD4L phosphorylation by JNK1 is required for this process. Conclusion: NEDD4L modulates Wnt signaling through a negative feedback mechanism. Significance: Our findings shed light on the understanding of Dishevelled2 stability control and NEDD4L-associated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 46 publications
8
101
0
Order By: Relevance
“…In accordance with these findings, two other studies further demonstrated NEDD4L's suppression of Wnt signaling to be mediated by Dishevelled-2 (Dvl2), a pivotal transducer of Wnt signals [61,72]. After Wnt proteins/ligands bind to their receptors, the signal is transduced to Dishevelled phosphoproteins, a crucial node where Wnt signaling diverges into at least three major cascades: canonical (Wnt/β-catenin), Planar Cell Polarity (PCP) and Wnt/Ca 2+ [73].…”
Section: Nedd4l (Nedd4-2)supporting
confidence: 50%
See 1 more Smart Citation
“…In accordance with these findings, two other studies further demonstrated NEDD4L's suppression of Wnt signaling to be mediated by Dishevelled-2 (Dvl2), a pivotal transducer of Wnt signals [61,72]. After Wnt proteins/ligands bind to their receptors, the signal is transduced to Dishevelled phosphoproteins, a crucial node where Wnt signaling diverges into at least three major cascades: canonical (Wnt/β-catenin), Planar Cell Polarity (PCP) and Wnt/Ca 2+ [73].…”
Section: Nedd4l (Nedd4-2)supporting
confidence: 50%
“…NEDD4L has been implicated in the regulation of a number of central pathways in cancer, including TGF-β [59,60], Wnt [61,62] and EGFR [63] signaling pathways. NEDD4L negatively regulates TGF-β/BMP signaling by inducing ubiquitination-mediated degradation of TGF-β type I receptor (TGF-R1) and receptor-regulated Smad2 [59].…”
Section: Nedd4l (Nedd4-2)mentioning
confidence: 99%
“…It is well established that the stereotyped branching program is dependent on precise cross-talk among multiple signaling pathways, including SHH, FGF, WNT, BMP, and TGF-β (1, 2). A number of E3 ubiquitin ligases have been identified to regulate substrates within these signaling pathways, such as ITCH (targets protein patched homolog 1, SHH pathway), vHL [targets protein sprouty homolog 2 (SPRY2), FGF pathway], NEDD4 (targets fibroblast growth factor receptor 1, FGF pathway), RNF43 (targets transcription factor 4, canonical WNT pathway), NEDD4L (targets segment polarity protein dishevelled homolog DVL-2, canonical WNT pathway), TRIM36 (unknown, targets noncanonical WNT pathway), and SMURF1 and SMURF2 (target SMADs, TGF-β/BMP pathway) (5,38,39,(48)(49)(50)(51)(52). These factors may function together with RFWD2 to ensure order at the protein level during the construction of a functional lung.…”
Section: Discussionmentioning
confidence: 99%
“…We next tested it in an assay for the ubiquitination and degradation of the Dishevelled protein (Dvl). Dvl contains a PY motif and is a substrate for several members of the Nedd4 family (22)(23)(24)(25), which bind PY motifs via their WW domains. This was readily demonstrated by coexpression of Dvl2 with Smurf2 and other ligases.…”
Section: Significancementioning
confidence: 99%